The evolution of the microstructure and properties of ageable Al-Si-Zn-Mg alloy during the recycling of milling chips through powder metallurgy (2020)
Although long/continuous metallic chips are easily recycled by melting, this is not the casefor discontinuous milling chips. The present study aimed to reduce waste generation andto facilitate the use of this byproduct in order to obtain a metallic-oxide composite. Chipswere collected after machining Al-Si-Zn-Mg alloy parts, and powders were obtained throughgrinding processes. Grinding was performed at 45, 69, and 94 h, with grinding bodies/chipsvolume ratios of 6:1, 8:1, 10:1 and 12:1. The resulting powders were characterized by scanningelectron microscopy, laser granulometry, and X-ray diffraction. After grinding, the parti-cles were compacted and sintered, and hardness was evaluated. It was found that metallicpowder is formed through plastic deformation, hardening, fracture, and dynamic recrystal-lization. It was possible to obtain samples with lower apparent density and higher hardnessby powder metallurgy from Al-Si-Zn-Mg alloy chips than from the bulk. Powder was obtainedafter grinding, and samples were obtained by compacting and sintering. The higher hard-ness value was attributed to the presence of Al2O3formed in the particles during grinding,which acts as a second reinforcing phase in the sintered samples, and as a retardant ofintermetallic phase growing